Abnormalitas Larva Ikan Semah (Tor douronensis) dengan Kepadatan yang Berbeda - Saputra, Angga; Ghofur, Muarofah; Arifin, M. Yusuf (Universitas Batangahari Jambi, 2025)
Semah fish (Tor douronensis) is one of the commodities that has the potential to be developed. Currently, the production of larvae and seeds is still very difficult to increase. The slow growth of semah fish larvae is a factor that greatly affects the amount of seed production produced. This study aims to determine the optimal density in the larval maintenance of Semah fish (Tor douronensis). The research was conducted using a Complete Random Design (RAL) environmental design with 4 (four) treatments and 3 (three) replicates, each of which was a stocking density of 3 heads/liter (A), stocking density of 6 heads/liter (B), stocking density of 9 heads/liter (C) and stocking density of 12 heads/liter (D). The fish used in this study were semah fish larvae measuring ± 1.00 cm and weighing approximately between 0.011–0.012 grams. The parameters observed in this study include abnormalities, and water quality. Based on the results of the study, the average abnormality of semah fish larvae ranges from 8.33% – 72.47%. The results of the water quality analysis of the maintenance media showed that the water quality was still in the decent range for the maintenance of semah fish larvae. Based on the results of the study, it can be concluded that the optimal density in the maintenance of semah fish larvae (Tor douronensis) is treatment A (3 fish/liter).